A non-randomised open-label exploratory ‘window of opportunity’ study of TG02 treatment in patients with locally advanced primary and recurrent RAS mutant colorectal cancer - Sara Roth; Kasmira Claire Wilson; Robert George Ramsay; Catherine Mitchell; Shienny Sampurno; Toan Duc Pham; Joseph Cherng Huei Kong; Stephen Q. Wong; Alexander Graham Heriot; Sanjeev Deva; Matthew Burge; Cecilie Sverdrup; et al. (Heliyon)
Background: TG02 is a peptide-based cancer vaccine eliciting immune responses to oncogenic codon 12/13 RAS mutations. This phase 1 clinical trial (NCT02933944) assessed the safety and immunological efficacy of TG02 adjuvanted by GM-CSF in patients with KRAS-mutant colorectal cancer. Methods: In the interval between completing CRT and pelvic exenteration, patients with resectable KRAS mutation-positive, locally advanced primary or current colorectal cancer, received 5–6 doses of TG02/GM-CSF. Immune response was defined as a positive delayed-type hypersensitivity or positive T cell proliferation assay response. Tumour biopsies were analysed for tumour-infiltrating lymphocytes (TILs) and blood for CEA and ctDNA. TILs and tumouroids were cultured, characterised and tested for their killing efficacy. Results: Six patients with rectal cancer were recruited to evaluate TG02. Three patients experienced a total of 16 treatment-related adverse events; all grade 1. Four of the 6 patients (66.7 %) had at least one vaccine-induced TG02 immune response. Flow cytometry analysis showed high proportion of PD-1-expressing TILs in 2 of 3 patient specimens’ post-treatment. A partial to near complete pathological response was reported in 4 of 6 patients. Conclusions: This study demonstrated that TG02/GM-CSF was well tolerated and induced a vaccine specific systemic immune response in the majority of patients. Low numbers limit conclusive clinical outcome reporting. High PD-1 expression on post-treatment TILs encourages the addition of an immune checkpoint inhibitor to TG02 and potentially other studies of peptide vaccines in future studies.